Viabilidade econômica de usina de reciclagem de resíduos da construção civil: estudo de caso da USIBEN - João Pessoa/PB - Sobralv, Ricardo Franklin Cavalcanti (2012)
The civil construction industry is the productive sector which produces the largest amount of solid waste. The reuse of waste generated from construction and destruction by the civil construction industry provokes, both directly and indirectly, a reduction on the use of nonrenewable resources, the generation of new solid waste, the waste of construction materials, the electric energy consumption itself, and also contributes for a considerable reduction on environmental impact, commonly a result of bad disposal of those materials on urban soil. Within these principles and because of the resolution #307 from CONAMA, João Pessoa s prefecture also known as PMJP - located on the state of Paraíba, created the System for the Sustainable Management of Civil Construction and Demolition Waste and the Integrated Plan of Civil Construction Waste Management, through municipal law #11,176/2007, enabling the construction of the Civil Construction Waste Benefiting Plant, or USIBEN, in the year 2007. The plant is capable of processing up to 20 tons of waste per hour. All the aggregate produced by USIBEN is used by the prefecture itself, which is the one in charge of the plant. In this project, more detailed research on the productive process of the plant was developed, trying to assess the enterprise on its financial viability. Many methods of economic analysis were used, with the help of statistics given directly by the plant and by EMLUR/PMJP. It was possible to discover the cost of the recycled waste aggregate, which reached, in 2008, R$17.39 (Seventeen reais and thirty nine centavos) per square meter, being also called profit point. The Net Present Value (NPV) found, considering a planning horizon of 20 years, was R$1,292,424.77 (one million two hundred ninety two thousand four hundred twenty four reais and seventy seven centavos), which is considered to be an effective method using the financial viability calculation for enterprises from this nature. In the same situation, the time spent until the return of investment was 3.24 years, considering, in the calculations, the Net Present Value on the projected period. The Benefit-Cost Rate found resulted in 2.61, whereas the Internal Rate of Return (IRR) was 26.24%, considering a scenario where the contribution for transportation of waste volumes received by the plant was ignored. On a second Scenario, was taken into account the contribution, to the gross income, of the entire avoided estimated costs of transportation of all volume of CCW received by the plant, being, in this case, the economic rates even better, proving the financial viability of the enterprise in the second simulation as well. This study serves as a guiding element to be used by the public manager, helping him to take wise decisions on matters related to the USIBEN and, consequently, to the construction waste management itself, in the city of João Pessoa.